HuR promotes castration-resistant prostate cancer progression by altering ERK5 activation via posttranscriptional regulation of BCAT1 - Hang You; Guojing Song; Zhizhen Xu; Saipeng Chen; Wenhao Shen; Heting Liu; Bingqian Deng; Jun Li; Gang Huang (Journal of Translational Medicine, 2024)
Abstract Background Castration-resistant prostate cancer (CRPC) is refractory to hormone treatment, and the underlying mechanism has not been fully elucidated. This study aimed to clarify the role and mechanism of Human antigen R (HuR) as a therapeutic target for CRPC progression. Methods HuR was knocked out by Cas9 or inhibited by the HuR-specific inhibitor KH-3 in CRPC cell lines and in a mouse xenograft model. The effects of HuR inhibition on tumour cell behaviors and signal transduction were examined by proliferation, transwell, and tumour xenograft assays. Posttranscriptional regulation of BCAT1 by HuR was determined by half-life and RIP assays. Results HuR knockout attenuated the proliferation, migration, and invasion of PC3 and DU145 cells in vitro and inhibited tumour progression in vivo. Moreover, BCAT1 was a direct target gene of HuR and mediated the oncogenic effect of HuR on CRPC. Mechanistically, HuR directly interacted with BCAT1 mRNA and upregulated BCAT1 expression by increasing the stability and translation of BCAT1, which activated ERK5 signalling. Additionally, the HuR-specific inhibitor KH-3 attenuated CRPC progression by disrupting the HuR-BCAT1 interaction. Conclusions We confirmed that the HuR/BCAT1 axis plays a crucial role in CRPC progression and suggest that inhibiting the HuR/BCAT1 axis is a promising therapeutic approach for suppressing CRPC progression. Graphical Abstract